Diastolic function of the left ventricle in patients with cardiomyopathy and low ejection fraction: the role of torsion in left bundle branch block - E. N. Pavlyukova; D. A. Kuzhel; G. V. Matyushin; V. S. Lytkina (Рациональная фармакотерапия в кардиологии)
Influence of left bundle branch block (LBBB) on left ventricle (LV) diastolic function and mechanisms of LV torsion remains underestimated.Aim. To study the relationship of LV diastolic function and LV torsion in patients with cardiomyopathy and LBBB in comparison with patients with cardiomyopathy and normal intraventricular conduction.Material and methods. Patients with cardiomyopathy (n=74) and LV ejection fraction <40% were included into the study and divided in two groups with narrow QRS complex and LBBB (the mean QRS duration = 153 ms). Echocardiography was performed in all patients with hemodynamic indices detection, and myocardium strain and torsion estimation.Results. The patients with LBBB showed less twisting, than patients without LBBB (3.24±3.35° and 5.87±3.83°, respectively, p=0.013914), but significant diastolic function differences between groups were absent. Despite the lack of difference in heart remodeling indices, subgroup of patients with LV rigid body rotation showed significantly less LV twisting and changes in pulmonary vein flow related to LV high end diastolic pressure. In the rigid body rotation group systolic left atrial filling fraction was 32.3±8.07%, whereas in the group with a physiological counter-rotation - 53.1±10.1% (p=0.000226). Potential reason of these findings was interventricular dyssynchrony. Deviation of time interval to peak myocardial systolic velocity between opposite basal segments in group with LBBB and anomalous LV rotation was more (63.3±35.1 ms) than this in group with LBBB and physiological LV rotation (8.0±17.9 mc, p=0.015922). This finding suggests that LV rigid body rotation in patients with LBBB may reflect a more pronounced mechanical dyssynchrony.Conclusion. LBBB has complex negative influence on process of LV electric activation and contraction which results in deterioration of LV twisting, mechanical dyssynchrony and deterioration of diastolic function. In disorders of intraventricular conduction and local contractility, assessment of pulmonary vein flow, possibly, more precisely reflects diastolic function status.